TANGGUNG JAWAB HUKUM PPAT ATAS PEMBUATAN AKTA JUAL BELI HAK ATAS TANAH BERSERTIPIKAT YANG DIBATALKAN OLEH PENGADILAN (STUDI PUTUSAN MAHKAMAH AGUNG NO.1138.K/PDT/2012 - R. RAMADIPTA (PREMISE LAW JURNAL, 2017)
Abstract Certified land right transfer through transact has to be done by public official, PPAT, in an authentic certificate; in this case, AJB (Sales Contract). When the case above is not done through AJB signed by PPAT, the process of transferring title of ownership of the land from the seller and the buyer cannot be processed in the Land Office. The research used juridical normative method on the prevailing law. The result of the research shows that sales contract on certified land drawn up by PPAT and has been revoked by the Court will be illegal and has no legal force to be used as an authentic certificate in sales contract. It cannot be used for a transferring title, from the seller to a buyer, in the Land Office. PPAT is liable for the revocation of the Sales Contract since it was illegal. The liability is in the form of compensation for the harmed party because of the revocation of the Sales Contract by the Court when the harmed party files the complaint to the Court and accepted by the Court as final and conclusive..   Keywords: PPAT, Sales Contract, Revoked by the Court